1997
DOI: 10.1097/00005768-199711000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic differences between athletes and nonathletes: spectral analysis approach

Abstract: The purpose of this study was to assess the adaptive effects of endurance training on autonomic function in athletes with spectral analysis of cardiovascular variability signals. Continuous ECG, arterial blood pressure (ABP), and respiratory signals were recorded from 15 athletes (VO2max > 55 mL.min-1.kg-1) and 15 nonathletes (VO2max < 45 mL.min-1.kg-1) during 10 min at sitting position. Autonomic function was assessed by low frequency power (LF power: 0.06-0.14 Hz) and high frequency power (HF power: the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
0
12

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 22 publications
2
79
0
12
Order By: Relevance
“…Alterations in the cardiac autonomic balance and changes in the intrinsic mechanisms acting on the sinus node are reported to contribute to this phenomenon. Human studies that have used cardiac autonomic blockade to investigate the effect of training on autonomic balance, reported the enhanced parasympathetic and/or diminished sympathetic activity on heart might contribute in part to the resting bradycardia [6,12]. The present study also indicates alterations in the autonomic control of the heart as it was evident by HRV analysis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Alterations in the cardiac autonomic balance and changes in the intrinsic mechanisms acting on the sinus node are reported to contribute to this phenomenon. Human studies that have used cardiac autonomic blockade to investigate the effect of training on autonomic balance, reported the enhanced parasympathetic and/or diminished sympathetic activity on heart might contribute in part to the resting bradycardia [6,12]. The present study also indicates alterations in the autonomic control of the heart as it was evident by HRV analysis.…”
Section: Discussionsupporting
confidence: 62%
“…Some have shown that endurance-trained subjects present higher values of power spectral HRV, indicating increasing vagal activity [6,7]; others have reported higher values of the LF component of HRV suggesting higher sympathetic activity [8]. Lower levels of sympathetic IJBR (2015) 6 (09) www.ssjournals.com activation [9] and vagal activation [8] and, finally, no differences have been found between trained and untrained subjects [10].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have reported an increase in the magnitude of this variable in the time domain (9), in the frequency domain others have reported absence of modifications (10), and an increase (11) or decrease (12) of sympathovagal balance in the sinus node.…”
Section: Introductionmentioning
confidence: 94%
“…It is known that endurance athletes have lower average resting heart rates than non-exercising individuals. 33,50 However, other exercise-induced autonomic influences on cardiac control are far more controversial.Autonomic control via sympathetic and parasympathetic modulation of the heart has been assessed by power spectral analysis of HRV 1,7,33,41,46,48,50 and BPV. 44,52 Different frequency peaks reflect specific physiological stimuli and it is possible to estimate the involvement of the autonomic nervous system (ANS) influence and balance in heart rate (HR) regulation.…”
mentioning
confidence: 99%